Universiti students’ view of self-directed learning in an online learning context - Mohamad Nasri, Nurfaradilla; FARIDAH, MYDIN K. (Advances in Social Sciences Research Journal, 2017)
Many studies have been carried out to enhance our understanding of self-directed learning (SDL). Although there is no shortage of research on SDL among adults and university students, there have been limited efforts towards investigating SDL within an online learning context, particularly from students perspectives. The purpose of this research was to explore self-directed learning (SDL) in the context of online learning from university students point of view. A constructivist grounded theory approach was used to inform the methodology and analytical framework of this study. Thirty postgraduate students were interviewed to obtain their views and experiences of being supervised for their research project in an online learning context. Students views and experiences are explored in terms of their readiness for SDL and the process of SDL experienced by them. The findings suggest that students SDL skills was closely related to their ability in using technology, access to technology and time spent using technology. Furthermore, a large majority of the students view SDL as a flexible way of learning in which the students act as the key agent of determining his or her own learning needs, strategies and pace. This study concludes by recommending that future research (i) explores the factors promoting and inhibiting SDL in an online context of SDL and (ii) investigates the essential online learning support needed to enhance students SDL abilities.